The Impact of Early Nutrition Following Peroral Endoscopic Myotomy in Achalasia: A Tertiary Center Experience - Buyruk, Abdullah Murat; Erdoğan, Çağdaş; Tekin, Fatih (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This retrospective single-center study aimed to assess the safety of early feeding in patients who met certain criteria following peroral endoscopic myotomy (POEM). Materials and Methods: Data from 100 patients who underwent POEM at our center between January and December 2022 were collected. Early feeding was defined as the introduction of clear liquid foods at 4 hours post procedure. At 4 and 24 hours, the pain was rated using the visual analog scale (VAS) in all patients. Patients without intraoperative complications (pneumoperitoneum requiring needle drainage, severe arterial bleeding requiring the use of hemostatic forceps, severe mucosal injury) and severe pain (VAS score 6) and nausea-vomiting at the fourth postoperative hour were given the early feeding approach. In patients who did not meet these requirements, enteral feeding was initiated after 24 hours (late feeding). Results: Among the 100 patients, 50 patients were categorized early feeding. No patients had a control esophagogram. In the early and late enteral feeding groups, VAS scores were 4 (0-6) and 6 (1-8) (P < .001) at 4 hours and 1 (0-3) and 1 (0-6) (P = .043) at 24 hours, respectively. No severe complications were developed after early feeding. The median hospital stay in the early feeding group was 1 (1-3) day. There was no emergency readmission in any of early feeding patients. Conclusion: Our study showed early feeding following POEM can be begun in achalasia patients who do not have intraoperative complications, severe pain, or nausea/vomiting. Cite this article as: Buyruk AM, Erdoğan Ç, Tekin F. The impact of early nutrition following peroral endoscopic myotomy in achalasia: A tertiary center experience. Turk J Gastroenterol. 2024;35(3):186-192.